PERILAKU SEKSUAL PRANIKAH MAHASISWA UNIVERSITAS “X” PELAKU CAM SEX DI KOTA SEMARANG - Mohammed Lukito Raja Puara; Priyadi Nugraha Prabamukti; Emmy Riyanti (Jurnal Kesehatan Masyarakat (Undip), 2019)
The total number of Indonesian internet users in 2017 was 143.26 million, an increase of 10.56 million in a year. Of the approximately 1.8 million Indonesians, 50% of them are unable to refrain from doing cybersex. Cybersex in terms of cam sex can be done remotely and can trigger premarital sexual behavior in adolescents. There were 26 cases of unwanted pregnancies and as many as 400 people with HIV / AIDS in Central Java, 70% of whom were adolescents who were affected by premarital sex in the 15-20 year age range in Semarang City. This study was to identify premarital sexual behavior of university "x" students as a result of cam sex in Semarang City. This research is qualitative study with data collection techniques based on observation and using in-depth interview techniques. The research subjects consisted of six university "x" students in Semarang City who did cam sex which eventually had premarital sex with their partner. What's interesting for them to do cam sex is because of curiosity and sexual drive. The attitude of research subjects who tend to be permissive so that premarital sexual behavior is a natural thing. Lack of communication with parents makes the subject of research hold on to life without any correction of their actions. Internet access that is so easy to get makes them able to do cam sex freely and the availability of places to support them for premarital sex. Lack of information about reproductive health or sexual behavior in the campus environment and the environment where the research subjects live, so they only know but do not really understand the impact of these behaviors.